CeO2 Structure Adjustment by H2O via the Microwave–Ultrasonic Method and Its Application in Imine Catalysis - Chang, Xijiang; Ding, Huihui; Yang, Jingxia (Frontiers in Chemistry, 2022)
CeO2 with fusiform structures were prepared by microwave-ultrasonic combined method, and their morphologies & surface structure were changed by simply adding different amount of H2O (1-5 mL) in the precursor system. The adding of H2O changed the PVP micelle structure and the surface state, resulting in CeO2 with different specific surface area (64-111 m2∙g-1) and Ce3+ defectes (16.5-28.1%). The sample with 2 mL H2O exhibited high surface area (111.3 m2∙g-1) and the relatively more surface defects (Ce3+%: 28.1%), resulting in the excellent catalytic activity (4.34 mmol∙g-1∙h-1) for imine synthesis, which is 2 times higher than that of the CeO2 sample prepared without H2O.